A Malaysian nation brand: the dissemination of it by Radio Malaya via the song Tanah Pusaka - Shazlin Amir Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2019)
A ‘nation branding’ project disseminates the reputation of a country, just as a company’s or product’s brand image is created through advertising and branding. This reputation has a profound impact on a country’s image and the way it is perceived. Increasingly countries are reinventing themselves and, in each time, repackaging its symbolisms for both internal and external audiences. This is essentially a nation branding effort that utilises symbols like colours, the national flower, the national anthem, military uniforms, medallions, rituals and patriotic songs. Radio Malaya, which began broadcasting in 1946, gradually developed into an arm for the propagation public service announcements, news, documentaries, interviews apart from music and songs upon the Federation of Malaya’s independence in 1957. With the establishment of Orkes Radio Malaya in 1961, popular patriotic songs began airing earnestly. This marks the beginning of the government’s intent in branding a national identity and making it identifiable in a sonic manner. This paper discusses the role of the popular patriotic song Tanah Pusaka (1964), in the process of branding the nation through the radio. It focuses on the importance of branding disseminated through the repetition of symbols in songs via the radio. The salient symbols and narrative of collective history embodied in this song are important in maintaining the survival and resilience of the ethnic that share the same collective history.